2010
DOI: 10.1007/s11270-010-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Induced Photocatalytic Degradation of Methyl Orange by Polythiophene/TiO2 Composite Particles

Abstract: The adsorption and photocatalytic degradation of methyl orange (MO) aqueous solution under visible light illumination by polythiophene/titanium dioxide (PTh/TiO 2 ) composite particles were studied. The experimental observations from UV-vis spectrophotometer indicate that MO molecules were degraded in a different degree during the visible light-induced photocatalysis reaction. We propose a new degradation mechanism of MO during the photocatalytic reaction, based on blue shift of UV-vis absorption spectra of MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…According to Akpan and Hameed [16] most study confirmed that the use of catalysts such as TiO2(SY) is effective for degradation at lower pHs, similar to the ones reported elsewhere, which is attributed to the strong electrostatic field of the Cs-TiO2(SY)/Glass photocatalyst enhancing photocatalytic performance between the surface of TiO2(SY) catalyst with positive charges, and the charges from solution, which is mostly negative [13,17]. However, lower pHs could adversely affect the catalyst during the photocatalytic process [16] making it necessary that the adsorption characteristics of MO on the surface of Cs-TiO2(SY)/Glass photocatalyst is investigated prior to the extended photodegradation process.…”
Section: Effect On Ph Of Pollutant Mediumsupporting
confidence: 77%
“…According to Akpan and Hameed [16] most study confirmed that the use of catalysts such as TiO2(SY) is effective for degradation at lower pHs, similar to the ones reported elsewhere, which is attributed to the strong electrostatic field of the Cs-TiO2(SY)/Glass photocatalyst enhancing photocatalytic performance between the surface of TiO2(SY) catalyst with positive charges, and the charges from solution, which is mostly negative [13,17]. However, lower pHs could adversely affect the catalyst during the photocatalytic process [16] making it necessary that the adsorption characteristics of MO on the surface of Cs-TiO2(SY)/Glass photocatalyst is investigated prior to the extended photodegradation process.…”
Section: Effect On Ph Of Pollutant Mediumsupporting
confidence: 77%
“…cOH + cO 2 À + dye + / colourless degraded products (8) Dye + (h VB + ) SWCNT/SSA doped PANI / colourless degraded products (9) The stability of PC2 has been further investigated by recycling the photocatalyst and the relative dye concentration versus irradiation time for four consecutive cycles is shown in Fig. 11(a) for RB and MO dye degradation.…”
Section: Photocatalytic Activity Studymentioning
confidence: 99%
“…Lots of investigations reported that 10-12% of dyes are used every year in textile industries such as Rose Bengal, Victoria blue, Thymol blue, Caramine, Indigo Red, Red 120, Rhodamine B, Methylene Blue, Eriochrome Black-T (EBT) [1][2][3][4] of which are major portion (20%) lost during synthesis and processing operations, which enter into water through effluents. The wastewater released from industries contains highly hazardous and coloured pigments which causes serious ill effect on aquatic life and also human beings [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%